Embedded coaxial bioprinting for vascular applications - Hong, Yixin (Nanyang Technological University, 2024)
In recent years, remarkable progress in biofabrication techniques has significantly enhanced the intricacy of tissue engineering. The integration of hydrogels with 3D printing has introduced unparalleled versatility in crafting biomimetic structures. Nonetheless, persistent challenges of fabricating small-diameter vascular grafts, particularly achieving continuous length fabrication, remain. As the foundational component of circulation, blood vessels constitute a complex infrastructure essential for the sustenance and viability of body tissues. Within artificial tissues and organs, the promotion of extensive vascularisation contributes significantly to enhanced tissue survival. This paper proposes an approach to fabricate continuous vascular grafts by combining extrusion-based horizontal coaxial printing with embedded printing, enabling simultaneous deposition of dual materials in a support matrix. Gelatine methacrylate (GelMA), known for its tuneable mechanical properties and hydrogel stability achieved through photocrosslinking, served as the vascular wall. The formation of chemical bonds induced by ultraviolet (UV) light confers additional stability to the hydrogel network. The gelatine printed in the coaxial core was dissolved, revealing a hollow channel within the GelMA scaffold, resembling blood vessels. Optimised printing conditions and parameters facilitate the successful fabrication of coaxial vasculature within the embedded bath. The post-printing photocrosslinking strategy of GelMA addresses issues related to differential light exposure encountered with in-situ photocrosslinking. This multifaceted approach addresses challenges in small-diameter vascular graft fabrication and streamlines the integration of hydrogel-based vascular structures into engineered tissues, offering a more efficient and effective solution in its applications. Increasing vascularisation and facilitating material exchange could improve cell survival within grafts, leading to enhanced implant outcomes.